2012
DOI: 10.1890/11-1600.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of decomposing litter and its microbial community to multiple forms of nitrogen enrichment

Abstract: Despite the importance of litter decomposition for ecosystem fertility and carbon balance, key uncertainties remain about how this fundamental process is affected by nitrogen (N) availability. Resolving such uncertainties is critical for predicting the ecosystem consequences of increased anthropogenic N deposition. Toward that end, we decomposed green leaves and senesced litter of northern pin oak (Quercus ellipsoidalis) in three forested stands dominated by northern pin oak or white pine (Pinus strobus) to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
163
5
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(186 citation statements)
references
References 59 publications
15
163
5
3
Order By: Relevance
“…Some experimental data indicate that high initial decomposition rates can result in slower organic matter decay at the later stages (Hobbie et al 2012). Such observations are perfectly reproduced by our model implementation, in which high initial decomposition rates lead to a change in molecular composition of the decomposing matrix that translates into a larger value of the intermolecular protection parameter, which, in turn, alters the decay process.…”
Section: Comparison With Existing Modelssupporting
confidence: 71%
“…Some experimental data indicate that high initial decomposition rates can result in slower organic matter decay at the later stages (Hobbie et al 2012). Such observations are perfectly reproduced by our model implementation, in which high initial decomposition rates lead to a change in molecular composition of the decomposing matrix that translates into a larger value of the intermolecular protection parameter, which, in turn, alters the decay process.…”
Section: Comparison With Existing Modelssupporting
confidence: 71%
“…Lignin is a key factor in the regulation of litter decomposition, especially during the later decay stage (Austin and Ballaré 2010). Excessive N inputs have been demonstrated to suppress ligninolytic enzyme activity in the long term and correspondingly reduce litter decomposition (Fog 1988;Carreiro et al 2000;Thirukkumaran and Parkinson 2000;Hobbie et al 2012), although a few studies have found no evidence of negative effects (Hobbie et al 2006). In the present study, lignin degradation was faster under the N30 treatment and slower under the N90 treatment than the control and slowed after 18 months of decomposition under all four treatments (Fig.…”
Section: Effects Of N Deposition and Management Practices On Litter Dmentioning
confidence: 99%
“…The effects of N addition on the activity of the soil microbial decomposers varied with the decay stage (Hobbie et al 2012;Tu et al 2012). In the early stage, N addition may increase the decomposers' activity (Molina et al 1983;Madritch and Hunter 2003) and promote N release.…”
Section: Effects Of N Deposition and Management Practices On Litter Nmentioning
confidence: 99%
“…The relative importance of residue chemistry, especially lignin, in the total amount and rate of residue decomposition is a function of N, which can both positively and negatively impact residue decomposition (Craine et al 2007;Hobbie et al 2012). These effects also differ depending on N source-residue N versus fertilizer N additions.…”
Section: Introductionmentioning
confidence: 99%